Community-based identification of ecosystem services in Ramsar wetlands: a socio-ecological network approach - González-Gamboa, Vladimir (2025)
Introduction: Ramsar wetlands are recognized worldwide for the ecosystem services they provide to society, for example they are source of food and water. However, the study of their socio-ecological complexity is often not focused on the local communities that directly interact with the ecosystem. However, the participation and involvement of local actors with wetland management authorities are key factors in achieving sustainability. Objective: To study the socio-ecological relevance of Ramsar wetland ecosystem services at the community level in Costa Rica. Methods: Information was collected from one participatory workshop, 27 interviews with community leaders, and a survey administered to 744 households. These methods were applied in 14 communities within seven Ramsar wetlands where interaction between the ecosystem and the communities is significant. Results: Provisioning ecosystem services were most frequently mentioned by local leaders and households. The main product quantified was fish harvesting, except for the Térraba-Sierpe wetland where mollusks were the most collected wetland product. The social network of wetland actors shows that public actors are the principal actors interacting positively with wetland authorities. The socio-ecological network of wetland-collected products identified central products. The fish families that are relevant simultaneously for many wetlands are robalo (Centropomidae), roncador (Haemulidae), and pargos (Lutjanidae). Additionally, the Caribe Noreste, Térraba-Sierpe, and Gandoca Manzanillo wetlands are those where more diversity and quantity of products were identified. Conclusions: The two socio-ecological networks highlight that two wetlands have conditions for high management tension, four have moderate tension, and only one has low tension for management.